Effects of estradiol on the cognitive function of postmenopausal women - Marinho, Ricardo M. (2008)
Objective: To analyze the effect of estrogen on the cognitive function of postmenopausal women through psychometric tests.Methods: Seventy-four postmenopausal women were divided into two groups: (G1) estrogen group (n = 34), treated with 2 mg 17 beta-estradiol; (G2) placebo group (n = 31), treated with inactive substance. All the participants were submitted, before and after treatment, to psychometric tests, Greene's Scale of Climacteric Symptoms and the Hamilton Scale for depression. Statistical analysis was performed using the Mann-Whitney test and Student's t-test. in order to evaluate the degree of improvement of symptoms or depression after estrogen treatment, Spearman's correlation coefficient was calculated.Results: A few psychometric tests (immediate and late recall of story, Trailmaking A and B, FAS, Stroop, Bells tests) showed post-intervention improvement, but these were not significant when compared to the placebo group's data. the estrogen group's climacteric symptoms were mitigated in comparison to placebo's, but there was no significant difference between the two groups on the Hamilton Scale. Reduction in climacteric symptoms was associated with improvement in executive function performance as evaluated by the Stroop test.Conclusion: Our results suggest estrogen improves the cognitive function, possibly due to a decrease in vasomotor symptoms. (C) 2008 Elsevier Ireland Ltd. All rights reserved.